Lymphomas associated with chronic hepatitis C virus infection: A prospective multicenter cohort study from the Rete Ematologica Lombarda (REL) clinical network. Issue 2 (22nd February 2019) - Rattotti, Sara; Ferretti, Virginia Valeria; Rusconi, Chiara; Rossi, Andrea; Fogazzi, Stefano; Baldini, Luca; Pioltelli, Pietro; Balzarotti, Monica; Farina, Lucia; Ferreri, Andrés J.M.; Laszlo, Daniele; Speziale, Valentina; et al.
Abstract: Chronic hepatitis C virus (HCV) infection is related with an increased risk of non‐Hodgkin lymphomas (NHL). In indolent subtypes, regression of NHL was reported after HCV eradication with antiviral therapy (AT). In 2008 in Lombardy, a region of Northern Italy, the "Rete Ematologica Lombarda" ( REL, Hematology Network of Lombardy—Lymphoma Workgroup ) started a prospective multicenter observational cohort study on NHL associated with HCV infection, named "Registro Lombardo dei Linfomi HCV‐positivi" ( "Lombardy Registry of HCV‐associated non‐Hodgkin lymphomas" ). Two hundred fifty patients with a first diagnosis of NHL associated with HCV infection were enrolled; also in our cohort, diffuse large B cell lymphoma (DLBCL) and marginal zone lymphoma (MZL) are the two most frequent HCV‐associated lymphomas. Two thirds of patients had HCV‐positivity detection before NHL; overall, NHL was diagnosed after a median time of 11 years since HCV survey. Our data on eradication of HCV infection were collected prior the recent introduction of the direct‐acting antivirals (DAAs) therapy. Sixteen patients with indolent NHL treated with interferon‐based AT as first line anti‐lymphoma therapy, because of the absence of criteria for an immediate conventional treatment for lymphoma, had an overall response rate of 90%. After a median follow‐up of 7 years, the overall survival (OS) was significantly longer in indolent NHL treated with AT as first line ( P  = 0.048); this confirms a favorable outcome in this subset. Liver toxicity was an important adverse event after a conventional treatment in 20% of all patients, in particular among DLBCL, in which it is more frequent the coexistence of a more advanced liver disease. Overall, HCV infection should be consider as an important co‐pathology in the treatment of lymphomas and an interdisciplinary approach should be always considered, in particular to evaluate the presence of fibrosis or necroinflammatory liver disease.